Advances in the biomedical application of polymer-functionalized carbon nanotubes. (21st May 2015) - Soleyman, Rouhollah; Hirbod, Sorina; Adeli, Mohsen
<x xml:space="preserve">Abstract</x> Water soluble carbon nanotubes as multivalent nanomaterials for biomedical applications have been discussed.